2020
DOI: 10.1055/s-0040-1713292
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices with Respect to Epilepsy among Nurses in the City of Niamey, Niger

Abstract: Objective The aim of this study is to evaluate knowledge, attitudes, and practices about epilepsy among nurses in the city of Niamey, Niger, to identify existing gaps in their knowledge concerning epilepsy to formulate recommendations to improve the quality of care for people with epilepsy. Materials and Methods We conducted a descriptive cross-sectional survey on epilepsy knowledge among nurses in the city of Niamey, using a self-administered questionnaire including questions related to knowledge about epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is to be noted that even lower estimates have been reported in the literature, a recent study published in 2020 conducted among nurses in Nigeria concluded that more than 77% of participants did not hear about epilepsy before, and almost 20% believed epilepsy was contagious. 21 However, an important limitation in the latter study is that despite the fact that all participants were healthcare workers, 74% of them were not bachelor degree holder nurses.…”
Section: Discussionmentioning
confidence: 86%
“…It is to be noted that even lower estimates have been reported in the literature, a recent study published in 2020 conducted among nurses in Nigeria concluded that more than 77% of participants did not hear about epilepsy before, and almost 20% believed epilepsy was contagious. 21 However, an important limitation in the latter study is that despite the fact that all participants were healthcare workers, 74% of them were not bachelor degree holder nurses.…”
Section: Discussionmentioning
confidence: 86%
“…A study conducted in 2020 in Niamey among 98 nurses showed that epilepsy was considered a demonic possession and a contagious disease by 9.2% and 19.4% of participants, respectively. 13 In the same study, epilepsy was considered an untreatable condition by 5.1% of the participating nurses.…”
Section: Sociocultural Aspectsmentioning
confidence: 98%
“…For example, epilepsy is thought to be due to witchcraft activity or demonic possession [15,22] or cannibalism [22]. In Niger, 9.7%, 3.4% and 38.6% of teachers studied considered epilepsy to be caused by witchcraft, possession by geniuses and impurity, respectively [1]. In a study in Ghana, [5] respondents mentioned bad spirits and witchcraft as causes of epilepsy.…”
Section: Introductionmentioning
confidence: 99%